Leptin controls hair follicle cycling. Issue 4 (April 2014) - Watabe, Reiko; Yamaguchi, Takashi; Kabashima‐Kubo, Rieko; Yoshioka, Manabu; Nishio, Daisuke; Nakamura, Motonobu
Abstract Leptin is a cytokine well known for its ability to control body weight and energy metabolism. Several lines of evidence have recently revealed that leptin also plays an important role in wound healing and immune modulation in skin. Sumikawa et al. Exp Dermatol 2014 evaluated the effect of leptin on hair follicle cycling using mutant and wild‐type mice. They report that leptin is produced in dermal papilla cells in hair follicles and that leptin receptor–deficient db/db mice show an abnormality in hair follicle cycling. Moreover, leptin injection induced the transition into the growth stage of the hair cycle (anagen). On this basis, it now deserves exploration whether leptin‐mediated signalling is a key stimulus for anagen induction and whether this may be targeted to manage human hair disorders with defect in the control of hair follicle cycling.